EFFECTS OF CANOLA OIL SUPPLEMENTED WITH ATHEROGENIC ELEMENT & NIGELLA SATIVA (KALONJI) ON SERUM LIPIDS IN ALBINO RATS - AN EXPERIMENTAL STUDY: Nigella Sativa (KALONJI) Effect on Serum Lipids - Ahmed, Mukhtar; Kousar, Naheeda; Abid, Sultan Muhammad; Farooq, Muhammad (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare effects of canola oil supplemented with atherogenic element and Nigella sativa on serum lipids in albino rats.Place and Duration of Study: Study was conducted at Pathology Department of Postgraduate Medical Institute, for 12 weeks.Study Design: ‘Laboratory based randomized controlled trials’.Material and Methods: Seventy two albino rats were selected and randomly divided into six groups of twelve animals with equal number of male and female in each. Fourteen days after acclimatization to the environment and basal diet, fasting blood samples (zero week) were collected by heart puncture under ether anesthesia and experimental diets were started which were continued for 12 weeks. All parameters were measured using enzymatic colorimetric methods.Results: Estimations of serum lipids showed increase in total cholesterol (TC) and High Density Lipoprotein Cholesterol (HDL-c) levels but fall in LDL-c concentrations in groups fed on canola oil diet. On the other hand, even atherogenic supplemented groups had decrease in cardio-protective HDL-c and raised LDL-c; although statistically non-significant. Thus canola oil diets were not hyperlipidaemic and prevented adiposity.  Nigella sativa (NS) diets significantly decreased serum total cholesterol and LDL-c while HDL-c was raised but non-significantly. Thus Nigella sativa prevented deposition of lipids in tissues, thus preventing tendency to obesity and atherogenesis by decreasing LDL-c in serum.Conclusion: Nigella sativa produces antilipidaemic and anti-obesity effects by decreasing low density lipoprotein cholesterol level which is statistically significant in two out of the three groups  fed on Ns; it also increased high density cholesterol  which was however non-significant in comparison with Canola oil alone.